PENGELOMPOKAN KABUPATEN-KOTA DALAM PRODUKSI DAGING TERNAK DI JAWA TENGAH TAHUN 2016 -2018 MENGGUNAKAN METODE MULTIDIMENSIONAL SCALING - Imam Desla Siena; Agus Rusgiyono; Dwi Ispriyanti (Jurnal Gaussian, 2020)
Animal husbandry is very important for the development of the welfare of the people of Central Java.the geographical conditions, Central Java is a suitable place to do livestock activities.Because of the increasing needs of livestock meat on the market, empowerment of livestock can be used as a livelihood to improve the economy of Central Java Comunity. This research is aimed at mapping the production of livestock meat in cities in Central Java both rural and urban areas. This study aimed to map existing health facilities in cities in West Java. The results of the analysis conducted by using Multidimensional Scaling analysis shows how grouping the cities in Central Java by its production of livestock meat. From the mapping of the cities there are three groups that have similarities among its members but different from the other groups.Each group formed have similar characteristics of a number of production of livestock meat.